Penerapan Strategi Pengajaran berdasarkan Pengalaman Siswa untuk Meningkatkan Hasil Belajar Passing Bawah Bolavoli pada Siswa Kelas VI SDN Pademawu Timur 5 Pamekasan - Ashari, Chobir; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to analyze the effect of implementing a student-experience-based teaching strategy on improving the learning outcomes of volleyball underhand passing skills in sixth-grade students of SDN Pademawu Timur 5 Pamekasan. The research method used was an experiment with a quantitative descriptive approach, using a one-group pretest-posttest design. Data collection was carried out through an underhand passing skill test using the French-Cooper procedure. The results of the analysis showed an increase in learning outcomes of 12.46% after the implementation of the strategy. Thus, the student-experience-based teaching strategy proved effective in improving underhand passing skills in volleyball.